Modeling college major choices using elicited measures of expectations and counterfactuals - Peter Arcidiacono; V. Joseph Hotz; Songman Kang (Institute for the Study of Labor (IZA), 2010)
The choice of a college major plays a critical role in determining the future earnings of college graduates. Students make their college major decisions in part due to the future earnings streams associated with the different majors. We survey students about what their expected earnings would be both in the major they have chosen and in counterfactual majors. We also elicit students' subjective assessments of their abilities in chosen and counterfactual majors. We estimate a model of college major choice that incorporates these subjective expectations and assessments. We show that both expected earnings and students' abilities in the different majors are important determinants of student's choice of a college major. We also show that students' forecast errors with respect to expected earnings in different majors is potentially important, with our estimates suggesting that 7.5% of students would switch majors if they made no forecast errors.
Keywords: I2; C81; 330; Choice of college major; subjective expectations; Studienfach; Bildungsverhalten; Studierende; Berufswahl; Einkommen; Erwartungstheorie; Schätzung; USA